Seaweeds as emerging functional foods and therapeutics for colorectal cancer management - Ashwini Gengatharan; Nur Vaizura Mohamad; Che Nur Mazadillina Che Zahari; Ramya Vijayakumar (Discover Food)
Abstract Seaweeds are rich in bioactive compounds that contribute to overall health and may reduce the risk of chronic diseases when consumed regularly as part of a balanced diet. Seaweeds have garnered significant attention for their potential as natural sources of anticancer agents, particularly in the treatment of colorectal cancer (CRC). Beyond their therapeutic applications, seaweeds offer significant potential as functional foods that could help prevent CRC, particularly in populations affected by poor dietary habits. This review explores the diverse bioactive compounds derived from seaweeds, including polysaccharides, polyphenols, and peptides, which have demonstrated efficacy against CRC in both in vitro and in vivo studies. These compounds exert anticancer effects through multiple mechanisms, such as inducing apoptosis, arresting the cell cycle, inhibiting metastasis, and modulating key cancer-related signalling pathways. Clinical trials have begun to investigate the therapeutic potential of seaweed bioactives, though large-scale studies remain limited. Despite the promising biological activities of these compounds, several challenges hinder their clinical translation. The complex molecular structures of seaweed-derived compounds often limit their bioavailability, as evidenced by in vitro gastrointestinal models showing low oral bioaccessibility. Furthermore, variability in extraction methods and environmental factors can impact the consistency and potency of these compounds, complicating their use in standardized treatments. Advances in drug delivery systems, such as nanoparticles and hydrogels, offer potential solutions to improve the targeted delivery and efficacy of these compounds in CRC treatment. This review emphasizes the need for further research into the pharmacokinetics, pharmacodynamics, and safety of seaweed-derived compounds. Addressing these challenges will be essential to fully harness the dual role of seaweeds as both preventive functional foods and therapeutic agents in CRC management, paving the way for more effective and less toxic cancer therapies.